2017
DOI: 10.1016/j.transci.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The watching-eyes phenomenon and blood donation: Does exposure to pictures of eyes increase blood donation by young adults?

Abstract: This study examined the effectiveness of exposure to a "watching-eyes image" in increasing blood donation rates among young people, a segment of the population that is particularly underrepresented among blood donors. Participants were 454 first-year university students, each of who was given a blood-donation flyer at the beginning of a lecture. Participants were randomly assigned to one of two conditions depending on whether the flyer they received bore a picture of eyes (experimental condition) or a neutral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…For example, eye images had prosocial effects such as cooperation for the clearing of trays in a university cafeteria ( Ernest-Jones et al , 2011 ) and for waste sorting at a bus stop ( Francey and Bergmüller, 2012 ). Similar results were found in experiments in more specific contexts such as blood donations: While eye images on flyers did not result in differences in pledge with a logo as control, more “real” donations were made by students who got the flyers with eyes image ( Sénémeaud et al , 2017 ). Other than the activation of a “sense of being seen” ( Pfattheicher and Keller, 2015 ) or the desire to maintain a pro-social reputation ( Bateson et al , 2006 ), it is important to note that humans possess neurons that respond to faces and eyes and activate such prosocial behaviors ( Emery, 2000 ; Haxby et al , 2000 ).…”
Section: Introductionsupporting
confidence: 77%
“…For example, eye images had prosocial effects such as cooperation for the clearing of trays in a university cafeteria ( Ernest-Jones et al , 2011 ) and for waste sorting at a bus stop ( Francey and Bergmüller, 2012 ). Similar results were found in experiments in more specific contexts such as blood donations: While eye images on flyers did not result in differences in pledge with a logo as control, more “real” donations were made by students who got the flyers with eyes image ( Sénémeaud et al , 2017 ). Other than the activation of a “sense of being seen” ( Pfattheicher and Keller, 2015 ) or the desire to maintain a pro-social reputation ( Bateson et al , 2006 ), it is important to note that humans possess neurons that respond to faces and eyes and activate such prosocial behaviors ( Emery, 2000 ; Haxby et al , 2000 ).…”
Section: Introductionsupporting
confidence: 77%
“…The results reported here clearly showed that the eye cues increased the frequency of punishment, even it requires immediate costs. At first glance, such fact might seem unexpected, but it matches with related findings showing that eye cues can engender behaviors that, though seemed to be problematic for themselves, actually work to enhance prosociality (e.g., Burnham and Hare, 2007;Sénémeaud et al, 2017). Prior work studying the decision-making process in the dictator game suggested that such decisions are led by two-step process.…”
Section: Discussionsupporting
confidence: 58%
“…For example, eye images had prosocial effects such as cooperation for the clearing of trays in a university cafeteria (Ernest-Jones et al, 2011) and for waste sorting at a bus stop (Francey and Bergmüller, 2012). Similar results were found in experiments in more specific contexts such as blood donations: While eye images on flyers did not result in differences in pledge with a logo as control, more "real" donations were made by students who got the flyers with eyes image (Sénémeaud et al, 2017). Other than the activation of a "sense of being seen" (Pfattheicher and Keller, 2015) or the desire to maintain a pro-social reputation (Bateson et al, 2006), it is important to note that humans possess neurons that respond to faces and eyes and activate such prosocial behaviors (Emery, 2000;Haxby et al, 2000).…”
Section: Introductionmentioning
confidence: 77%